2023
DOI: 10.1177/14799731231174542
|View full text |Cite
|
Sign up to set email alerts
|

Muscle oxygen utilization and ventilatory parameters during exercise in people with cystic fibrosis: Role of HbA1c

Abstract: Introduction Glycated hemoglobin can interfere with oxygen delivery and CO2 removal during exercise. Additionally, pancreatic insufficiency increases oxidative stress and exacerbates exercise intolerance in people with cystic fibrosis (PwCF). This investigation sought to test the hypotheses that elevated Hemoglobin A1c (HbA1c) can negatively affect exercise parameters in PwCF and that reductions in oxidative stress can improve tissue oxygenation in individuals with elevated HbA1c. Methods Twenty four PwCF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In line with our findings, Pastré et al (2014) andMarcotte et al (1986) showed that in patients with CF, nutritional status plays a significant role in determining exercise capacity, and malnutrition is an independent factor for lower exercise tolerance. Exocrine pancreatic insufficiency increases oxidative stress and exacerbates exercise intolerance in people with CF, as recently demonstrated byQuertermous et al (2023). Evaluating CF adults,Moço et al (2013) found no relationship between functional capacity measured by the 6MWT and any CFQ-R domains.…”
mentioning
confidence: 70%
“…In line with our findings, Pastré et al (2014) andMarcotte et al (1986) showed that in patients with CF, nutritional status plays a significant role in determining exercise capacity, and malnutrition is an independent factor for lower exercise tolerance. Exocrine pancreatic insufficiency increases oxidative stress and exacerbates exercise intolerance in people with CF, as recently demonstrated byQuertermous et al (2023). Evaluating CF adults,Moço et al (2013) found no relationship between functional capacity measured by the 6MWT and any CFQ-R domains.…”
mentioning
confidence: 70%